Ogilvie's syndrome in the postnatal period: a case series. (16th November 2010) - Salim, S; Stocker, L; Brackley, K
Abstract : Introduction: Acute colonic pseudo-obstruction or Ogilvie's syndrome is a rare complication of the puerperium, characterised by massive dilatation of the colon in the absence of mechanical obstruction1 2 3 4 . Information relating to morbidity and mortality arise from case reports or from the triennial maternal mortality reports, which inevitably involve more severe cases.5 Aim: To describe the presenting features, management and outcome of women with a clinical diagnosis of Ogilvie's syndrome. Design: A retrospective review of cases identified from High Dependency Unit records in a large university hospital over a 4 year period. Results: 11 cases were identified, all post Caesarean section of which 82% were emergencies. The most common presenting symptoms were abdominal pain and distension between day 1 and 3 postoperatively, in the absence of peritonism. Nine women had a caecal dilatation of 9 cm or more on abdominal x-ray or CT scan. Six cases (55%) resolved with conservative management that is, nasogastric tube, phosphate enemas or flatus tube. Three women (27%) underwent successful endoscopic decompression with rapid resolution of symptoms. Two women continued to have abdominal distension despite conservative management and eventually required emergency laparotomy and right hemi-colectomies, one due to bowel perforation and one due to non-viable bowel. Conclusion: Our series revealed that Ogilvie's syndrome post Caesarean section is associated with an 18% risk of laparotomy and major bowel surgery. Early identification is important with timely involvement of the general surgeons. The majority of cases resolve with conservative management but endoscopic decompression should be considered if distension persists.